2022
DOI: 10.1021/acs.biomac.2c00960
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Fluorescence in Peptide Amphiphile Micelles with Protein-Inspired Phosphate Sensing

Abstract: Although peptide amphiphile micelles (PAMs) have been widely studied since they were developed in the late 1990s, to the author's knowledge, there have been no reports that PAMs intrinsically fluoresce without a fluorescent tag, according to the aggregation-induced emission (AIE) effect. This unexpected fluorescence behavior adds noteworthy value to both the peptide amphiphile and AIE communities. For PAMs, intrinsic fluorescence becomes another highly useful feature to add to this well-studied material platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…It was calculated by comparing the fluorescence emission intensity integration versus absorbance for each PA system at various concentrations (Figure S10) to a tryptophan standard solution, which has a QY of 0.14 (Figure S11). C 16 VVAAK 2 had the highest QY at 0.17, which was significantly higher than those of all other systems, and an order of magnitude higher than the previous AIE PA system . C 16 AAGGK 2 and C 16 GGGGK 2 had the next highest QY values at 0.046 and 0.030, respectively.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…It was calculated by comparing the fluorescence emission intensity integration versus absorbance for each PA system at various concentrations (Figure S10) to a tryptophan standard solution, which has a QY of 0.14 (Figure S11). C 16 VVAAK 2 had the highest QY at 0.17, which was significantly higher than those of all other systems, and an order of magnitude higher than the previous AIE PA system . C 16 AAGGK 2 and C 16 GGGGK 2 had the next highest QY values at 0.046 and 0.030, respectively.…”
Section: Resultsmentioning
confidence: 79%
“…It has been shown that less mobile AIE molecules exhibit higher emission because more energy is converted into emission compared to kinetics . The proposed AIE mechanism of PA nanofibers is that the amide bonds in the peptide backbone constitute enough electron density such that when they are rigidly packed in the nanofiber corona, they exhibit AIE . This unexpected AIE has also been observed in other amide-based aggregates …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…As the irradiation pretreatment time increases, the luminescence intensity reached a maximum level (Figure c and Movie S2). We speculate that the luminescence properties of rPBDT spherulites are related to the formation of rigid disulfide hindering the rotation of benzene rings and the supramolecular structure of molecular chains. The necessity for UV pretreatment can be linked to the insufficiently dense arrangement of PBDT molecules. This lack of density stems from the rapid progression of step-growth polymerization and self-assembly processes, and UV irradiation may disrupt partial disulfide bonds, which leads to the reorganization of PBDT molecules within the spherulite for a more tightly packed structure.…”
Section: Resultsmentioning
confidence: 99%